The psychology of preaching: a literature review - Fontaine, Rodrigue Ancelot Harvey (2010)
This study focuses on improving the effectiveness of Muslim preachers (dai’e) by providing them with a theory of psychology that allows preachers to address the psychological issues of their audience. After reviewing various theories of personality, this author proposes Erickson‟s theory as the key theory that preachers can use to become more effective. The practicalities and implications of such an approach are discussed. The output of this study are six hypotheses that needs to be tested in subsequent studies.